Dinâmicas fronteiriças e formação no colégio agrícola em Foz do Iguaçu: entre oeste do Paraná, Brasil e leste do Paraguai - Marinoski, Laura Duarte (2021)
Having as a framework the concepto f school as a space constituted by a set of particular social and cultural experiences, articulated to regulations, norms and curricula and Other documents identified as essential, my objetive in this thesis is to highlight the technical professional education course of high school level in Agriculture at Colégio Agrícola de Foz do Iguaçu – PR in contexto. My argument is that the border specificity is constitutive of the school, observed in the complexity of the relationships between students, teachers, pedagogues, directors and inspectors who produce the contente for technical training closely articulated to immigration processes in western Paraná and eastern Paraguay, in movements from various directions to develop Family farming and large agribusiness companies that characterize this region. The relationship between the diferente groups are expressed in the formo f recruitment, in the organization of the boarding school, in the pedagogical relationships, in the oragnization of times, in the history and the physical location of the school. The field research, in person and with virtual resourcesm took place between July 2019 and December 2020, a period crossed by the pandemic, following trajectories, individual and collective experiences, attentive to the particular and the contingente of intersubjective experiences through descriptive exercises of the sensitive, life lived, memories and meanings of school. Based on this research, it was possible to conceive the school Community as both a national Project of economic and geopolitical interest, as well as a historically located and culturally oriented process, which is (re)done daily. The sense of school is linked to border relations, materialized in the students’ Family experiences and in extra-local forces – urban Community and State policies. Intertwined, these relationship configure the Agricultural College of Foz do Iguaçu.